2012
DOI: 10.1097/01.asw.0000414705.56138.65
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective, Single-Center, Nonblinded, Comparative, Postmarket Clinical Evaluation of a Bovine-Derived Collagen With Ionic Silver Dressing versus a Carboxymethylcellulose and Ionic Silver Dressing for the Reduction of Bioburden in Variable-Etiology, Bilateral Lower-Extremity Wounds

Abstract: Both CMC and BDC silver dressings appeared to have statistically similar efficacy regarding the rate of wound healing and little impact on the actual bioburden in chronic lower-extremity wounds. Interestingly, there was no correlation in the size of the wound and any effect on bioburden. Although the BDC dressing showed a higher absolute rate of wound closure, neither technology demonstrated a statistically significant difference in wound closure rate when corrected for initial wound size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 27 publications
1
14
0
5
Order By: Relevance
“…Manizgate et al reported that in a prospective study of two silverreleasing dressings, neither dressing had an impact on the level of bioburden identified in treated VLUs. 243 Conversely, in another study, Lantis and Gendics found that a sustained-release silver sulfadiazine foam reduced the level of bacteria cultured from infected VLUs, but there was no correlation with an improvement in wound size. 241 A Cochrane review on the use of topical silver for infected VLUs concluded that there is insufficient evidence to recommend the use of silver-containing dressings or topical agents for treatment of infected or contaminated chronic wounds.…”
Section: Wound Carementioning
confidence: 94%
“…Manizgate et al reported that in a prospective study of two silverreleasing dressings, neither dressing had an impact on the level of bioburden identified in treated VLUs. 243 Conversely, in another study, Lantis and Gendics found that a sustained-release silver sulfadiazine foam reduced the level of bacteria cultured from infected VLUs, but there was no correlation with an improvement in wound size. 241 A Cochrane review on the use of topical silver for infected VLUs concluded that there is insufficient evidence to recommend the use of silver-containing dressings or topical agents for treatment of infected or contaminated chronic wounds.…”
Section: Wound Carementioning
confidence: 94%
“…A large number of commercial collagen-based dressings is already available and some are specifically indicated for partial-and full-thickness pressure, venous, vascular and diabetic ulcers as is the case of BCG (Table 3). As reported in Table 2, recent studies have proved the efficacy of collagen and gelatin dressings for decreasing infection by bacteria and favoring granular tissue formation, stimulating faster wound healing in DFU patients [181][182][183][184]. Different approaches tested so far include the incorporation of glucose oxidase in a collagen matrix in order to achieve the sustained delivery of reactive oxygen species (ROS), natural compounds (such as polyphenols), growth factors (such as bFGF), antibiotics (such as doxycycline and levofloxacin) and ionic silver as antimicrobial agent [182,185,186].…”
Section: Cellulose and Its Derivativesmentioning
confidence: 99%
“…All studies were published between 2012 and 2019. Five types of antimicrobial collagen-based dressings were identified in the eight articles selected: (1) ( n = 3) gentamicin-loaded collagen dressing (Garamycin, Innocoll Pharmaceuticals Ltd. and Collatamp ® EG, Syntacoll, Germany) [ 51 , 52 , 53 ]; (2) ( n = 2) collagen dressing impregnated with antimicrobial polyhexamethylene biguanide (PHMB) (PuraPly AM, Organogenesis Inc., Canton, MA, USA) [ 54 , 55 ]; (3) ( n = 1) collagen with mixture of cellulose and silver (Promogran Prisma, Systagenix Wound Management Ltd., Skipton, UK) [ 56 ]; (4) ( n = 1) mixed collagen with gentian violet/methylene blue (Hydrofera Blue, Hollister Wound Care Inc, Libertyville, IL, USA) [ 57 ]; (5) ( n = 1) bovine-derived collagen impregnated with silver ions (Ag) (Puracol plus Ag, Medline Industries, Northfield, IL, USA) [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…The prospective clinical study by Manizate and co-researchers [ 58 ] compared the efficiency to reduce bacterial load between two products of sodium carboxymethylcellulose with 1.2% ionic silver (CMC) and bovine native collagen with 1.12% ionic silver (BDC). Silver (Ag) ions are known to be bactericidal by binding to the bacterial cell wall, respiratory and nutrition-involved proteins, and DNA—preventing the replication system [ 74 ].…”
Section: Resultsmentioning
confidence: 99%